Food processing : principles and applications - Clark, Stephanie, 1968- editor; Jung, Stephanie, editor; Lamsal, Buddhi, editor (Chichester, West Sussex, UK : John Wiley & Sons Inc., 2014)
Includes bibliographical references and index